Study on the Temperature, respiratory rate, heart rate and Electrocardiogram of concomitant administration of Maytenus macrocarpa “Chuchuhuasi” and Propranolol in escalating doses - Rommel, Zambrano-Huailla; Alexander, Zambrano-Huailla; Karelya, Wong-Peréz; Jorge, García-Berrocal; Tiara, Velit-Bassino; Dayana, Zevallos-Gonzáles; José, Mujica-Calderón; Alberto, Salazar-Granara (Pharmacognosy Communications)
Background: Previous studies of Maytenus macrocarpa “Chuchuhuasi” and linked species have corroborated their biological effects related to cardiovascular, respiratory, and others systems. This research has focused on evaluating the effect in the corporeal temperature, respiratory rate, heart rate and electrocardiogram of concomitant administration of “Chuchuhuasi” and propranolol in escalating doses. Methods: Albino rats were divided randomly into four control groups and five experimental groups. Temperature was measured by a digital thermometer, respiratory rate by direct-counting and electrocardiogram and heart rate by a Grass Polygraph. Rhythmic and arrhythmic electrocardiographic patterns were identified by a mathematical modeling of autocorrelation. The outcomes were acquired in periods of time but were analyzed using the average of the whole of the experiment. The result was applied to the following statistical tests: one-way ANOVA, Tuckey, Shapiro-Wilk, Pearson Correlation and Chi square with Yate’s correction test. Results: The comparison between control and experimental groups showed a profile of raise in the corporeal temperature, then, for the respiratory rate the bias was to increase, in contrast, it was showed trend to decrease of the heart rate and an increase of voltages of p and r wave, also, an increment of p-r interval and presences of arrhythmias. Conclusion: This study revealed effects of concomitant administration of propranolol and Maytenus macrocarpa on temperature, respiratory rate, heart rate and electrocardiogram. In addition, it showed abnormalities in the electrocardiogram which were associated with arrhythmia patterns Thus, the usage of propranolol and Maytenus macrocarpa may negatively impact several aspects of the health of users of these drugs.
Keywords: Chuchuhuasi; Propranolol; Heart rate; Respiratory rate; Tempera- ture; Arrhythmia